Digitization of Indigenous Knowledge: Focus on Ilorin Durbar Festival, Ilorin, Nigeria - Sulaiman, Kabir Alabi; Olarongbe, S. A. (Department Library of Governance Institut of Home Affairs, 2024)
Background: Festivals, whether religious, cultural, or secular, play an important role in society. It plays an important role in any local community because it contributes to the development of people's pride, culture, and identity in a particular community. Purpose: This study examines digitization of indigenous knowledge of Ilorin Durbar Festival, Ilorin Nigeria. Method: This study employed a narrative research design, using interview for data collection. Result: The study revealed that activities such as horse riding, the Ilorin anthem, Ijoolomo-Oba, and Keegbe Lulu (calabash beats), can be digitized, ensuring accessibility and future use through capturing devices like cameras, recording tapes, and compact discs. Conclusion: The study concludes that digitizing festivals like the Durbar allows it to be viewed and accessed by a larger global audience. The study recommends creating a committee to manage the digitization efforts for the Ilorin Emirate Durbar Festival and suggests announcing the program of events to the public before the festival day.